1997
DOI: 10.1084/jem.186.6.887
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Plasma Membrane Targeting of Grb2–Murine Son of Sevenless (mSOS) Complex and Differential Activation of the Fyn–T Cell Receptor (TCR)-ζ–Cbl Pathway Mediate T Cell Hyporesponsiveness in Autoimmune Nonobese Diabetic Mice

Abstract: Nonobese diabetic (NOD) mouse thymocytes are hyporesponsive to T cell antigen receptor (TCR)-mediated stimulation of proliferation, and this T cell hyporesponsiveness may be causal to the onset of autoimmune diabetes in NOD mice. We previously showed that TCR-induced NOD T cell hyporesponsiveness is associated with a block in Ras activation and defective signaling along the PKC/Ras/MAPK pathway. Here, we report that several sequential changes in TCR-proximal signaling events may mediate this block in Ras activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 46 publications
5
36
1
Order By: Relevance
“…A similar observation has been described for autoimmune nonobese diabetic mice, where it was shown that a decrease in the phosphorylation of a 36-kDa protein upon TCR engagement in hyporesponsive T lymphocytes correlates with a decreased membrane targeting of PLC␥1 and the Grb2/Sos complex, and an impaired activation of Ras (40,41). The current data indicate that in SF T lymphocytes from RA patients this phosphoprotein represents the membrane-anchored 36-kDa adaptor protein LAT.…”
Section: Discussionsupporting
confidence: 59%
“…A similar observation has been described for autoimmune nonobese diabetic mice, where it was shown that a decrease in the phosphorylation of a 36-kDa protein upon TCR engagement in hyporesponsive T lymphocytes correlates with a decreased membrane targeting of PLC␥1 and the Grb2/Sos complex, and an impaired activation of Ras (40,41). The current data indicate that in SF T lymphocytes from RA patients this phosphoprotein represents the membrane-anchored 36-kDa adaptor protein LAT.…”
Section: Discussionsupporting
confidence: 59%
“…In addition to the low CD86 expression in the NOD mouse described here, Delovitch and coworkers (15,16) have shown that signal transduction by the TCR-CD3 complex is defective in NOD, since the recruitment of Grb2, mSos, and PLC-␥1 to the cell membrane and activation of p21 ras upon TCR cross-linking are all diminished in NOD thymocytes. Therefore, the defective T cell proliferation and CTLA-4 up-regulation observed in NOD mice might be a consequence of the low CD86 levels in combination with the defective TCR-CD3 signaling previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…T cells from diabetic NOD mice and nondiabetic NOD mice at 18 wk of age are more susceptible to anti-CD3 (mitogenic and nonmitogenic)-induced AICD than T cells from 12-and 15-wk-old NOD mice. This may arise due to defective TCR signal transduction (41,42) that leads to decreased susceptibility to TCR-mediated activation and AICD in T cells from prediabetic NOD mice at 12 and 15 wk of age. These defects in NOD T cell signaling may also explain why a higher dose of anti-CD3 was required for the activation of NOD T cells than B6 T cells (43).…”
Section: Discussionmentioning
confidence: 99%